PENYELESAIAN SENGKETA TANAH PT.INECDA PLANTATION DENGAN MASYARAKAT ADAT SUNGAI PARIT DI INDRAGIRI HULU - Seftirizanda, Yarizkha; ', Firdaus; Hendra, Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Problems that occur between is a 42 Ha land dispute villagers Sungai Parit, district Indragiri Hulu Sungai Lala with PT.Inecda Plantation.Masyarakat claims that about 42 hectares of land belongs to the people while PT.Inecda Plantation claims that 42 ha of land that are owned by the company the. Plantation PT.Inecda related dispute with residents of Sungai Parit causing residents sent a letter to the Regional Representatives Council Indragiri Hulu. The letter sent to residents of the Regional Representatives Council Indragiri Hulu in connection with PT.Inecda Plantation since 20 years ago to annex the land warga.Surat sent due to lack of clarity on the settlement that has been done several times with the Government of Indragiri Hulu. The purpose of this thesis, namely: First, to find out what the causes of land disputes between indigenous peoples PT.Inecda Plantation with moat river, Secondly, to find out how the efforts made for the settlement of land disputes with indigenous peoples PT.Inecda Plantation river trench.This type of research can be classified in this type of sociological research is research done by identifying how the effectiveness of law that law applies in the community.From the research it is clear that the cause of the problem of land disputes with indigenous peoples PT.Inecda Plantation River Ditch is due to the inclusion of a new home or investment of PT.Inecda Plantation namely household money. PT.Inecda Plantation as well as ignoring the rights of indigenous peoples and the Government Sungai Parit not firm in see investments coming in, a local company established itself so that the environment of indigenous people ignoring local area and do not pay attention to the condition of the area where they founded the company. The settlement of land disputes with indigenous peoples PT.Inecda Plantation Sungai Parit is the first mediation session conducted on January 15, 2013 Date mediated by the head of the Sungai Parit in Hall Village Head Office, On January 10, 2004 Local Government conduct a second mediation process mediated by the head of the Regional land Indragiri Hulu, As of February 15, 2016 at a meeting held by the National land Agency and the Ministry of Environment held diaur china to listen to the opinions of indigenous peoples Sungai Parit against customary land tilled by PT.Inecda Plantation. The results of the meeting the majority of customary land Sungai Parit people returned to the Ministry of Environment to manage. Keywords : Settlement-Limited-Indigenous